Exposure to low doses of Coxiella burnetii caused high illness attack rates: Insights from combining human challenge and outbreak data - Brooke, Russell John; Mutters, Nico T. (Epidemics, 2015)
As a major zoonotic pathogen, characterization of the infectivity and pathogenicity of Coxiella burnetii is essential to understand Q-fever epidemiology. We want to extend a recently published human dose response model based on experimental challenge of young adult males to include other age groups and both genders. Additionally, we can estimate the spatial distribution of exposure based on observed outbreak data. Dose response assessment based on human challenge, is extended by including outbreak data, using location of cases as a proxy for exposure. This allows estimation of the influence of age and gender on the probability of developing symptoms of acute respiratory illness. In an outbreak in Switzerland, in 1983, exposure to C. burnetii was shown to depend strongly on distance from the source. The susceptibility of males to develop Q-fever decreases with age, while in females, middle-aged women appear to have the lowest risk. The published dose response model for Q-fever, based on experimental challenge of a small group of human volunteers, has been updated with data from a well studied outbreak. Infectivity estimates remain high, and even low doses (of 10 or fewer organisms) cause a high risk of illness.